Cardiometabolic health and per and polyfluoroalkyl substances in an Inuit population - Aker, Amira; Ayotte, Pierre; Caron-Beaudoin, Élyse; Ricard, Sylvie; Gaudreau, Éric; Lemire, Mélanie (Environment International, 2024)
Introduction: The cardiometabolic health status of Inuit in Nunavik has worsened in the last thirty years. The high concentrations of perfluoroalkyl acids (PFAAs) may be contributing to this since PFAAs have been linked with hypercholesterolemia, diabetes, and high blood pressure. The aim of this study was to examine the association between a PFAAs mixture and lipid profiles, Type II diabetes, prediabetes, and high blood pressure in this Inuit population. Methods: We included 1212 participants of the Qanuilirpitaa? 2017 survey aged 16–80 years. Two mixture models (quantile g-computation and Bayesian Kernel Machine Regression (BKMR)) were used to investigate the associations between six PFAAs (PFHxS, PFOS, PFOA and three long-chain PFAAs (PFNA, PFDA and PFUnDA)) with five lipid profiles and three cardiometabolic outcomes. Non-linearity and interaction between PFAAs were further assessed. Results: An IQR increase in all PFAAs congeners resulted in an increase in total cholesterol (β 0.15, 95% confidence interval (CI) 0.06, 0.24), low-density lipoprotein cholesterol (LDL) (β 0.08, 95% CI 0.01, 0.16), highdensity lipoprotein cholesterol (HDL) (β 0.04, 95% CI 0.002, 0.08), apolipoprotein B-100 (β 0.03, 95% CI 0.004, 0.05), and prediabetes (OR 1.80, 95% CI 1.11, 2.91). There was no association between PFAAs and triglycerides, diabetes, or high blood pressure. Long-chain PFAAs congeners were the main contributors driving the associations. Associations were largely linear, and there was no evidence of interaction between the PFAAs congeners. Conclusions: Our study provides further evidence of increasing circulating lipids with increased exposure to PFAAs. The increased risk of prediabetes points to the influence of PFAAs on potential clinical outcomes. International regulation of PFAAs is essential to curb PFAAs exposure and related health effects in Arctic communities.